Corrigendum to: Establishment and In Vitro Evaluation of Porous Ion-Responsive Targeted Drug Delivery System. Protein & Peptide Letters, volume 27(11), (2020). - Liu, Hongfei; Zhu, Jie; Bao, Pengyue; Ding, Yueping; Wang, Jiapeng; Du, Yi; Qu, Yang; Xu, Ying (Protein and Peptide Letters, 2021)
The authors are regretful for submitting and approving the publication of incorrect Figure 4 in this article. Below is the corrected version along with the revised caption. The electronic version of the article has already been corrected.